Configurations of Plague: Spatial Diagrams in Early Epidemiology. Issue 4 (1st December 2019) - Engelmann, Lukas
Abstract : Diagrams are found at the heart of the modern history of epidemiology. Epidemiologists used spatial diagrams to visualize concepts of epidemics as arrangements of biological, environmental, historical, as well as social factors and to analyze epidemics as configurations. Often, they provided a representation of the networks of relationships implied by epidemics, rather than to offer conclusions about origin and causation. This article will look at two spatial diagrams of plague across a period in which an epidemiological way of reasoning stood in stark contrast to arguments provided about plague in the rising field of bacteriology and experimental medicine. This historical genealogy of epidemiologists working with diagrams challenges perceptions of epidemic diagrams as mere arguments of causality to emphasize diagrammatic notions of uncertainty, crisis, and invisibility.